An AM‐induced, MYB‐family gene of Lotus japonicus (LjMAMI) affects root growth in an AM‐independent manner. (31st December 2012) - Volpe, Veronica; Dell'Aglio, Elisa; Giovannetti, Marco; Ruberti, Cristina; Costa, Alex; Genre, Andrea; Guether, Mike; Bonfante, Paola
Summary The interaction between legumes and arbuscular mycorrhizal (AM) fungi is vital to the development of sustainable plant production systems. Here, we focus on a putative MYB‐like (LjMAMI) transcription factor (TF) previously reported to be highly upregulated in Lotus japonicus mycorrhizal roots. Phylogenetic analyses revealed that the protein is related to a group of TFs involved in phosphate (Pi) starvation responses, the expression of which is independent of the Pi level, such as PHR1. GUS transformed plants and quantitative reverse transcription PCR revealed strong gene induction in arbusculated cells, as well as the presence of LjMAMI transcripts in lateral root primordia and root meristems, even in the absence of the fungus, and independently of Pi concentration. In agreement with its putative identification as a TF, an eGFP‐LjMAMI chimera was localized to the nuclei of plant protoplasts, whereas in transgenic Lotus roots expressing the eGFP‐LjMAMI fusion protein under the control of the native promoter, the protein was located in the nuclei of the arbusculated cells. Further expression analyses revealed a correlation between LjMAMI and LjPT4, a marker gene for mycorrhizal function. To elucidate the role of the LjMAMI gene in the mycorrhizal process, RNAi and overexpressing root lines were generated. All the lines retained their symbiotic capacity; however, RNAi root lines and composite plants showed an important reduction in root elongation and branching in the absence of the symbiont. The results support the involvement of the AM‐responsive LjMAMI in non‐symbiotic functions: i.e. root growth.